Mitochondrial Dysfunction in Advanced Liver Disease: Emerging Concepts - Zhang, Ingrid W.; López-Vicario, Cristina; Duran-Güell, Marta; Clària, Joan (Frontiers in Molecular Biosciences, 2021)
Mitochondria are entrusted with the challenging task of providing energy through the generation of ATP, the universal cellular currency, thereby being highly flexible to different acute and chronic nutrient demands of the cell. The fact that mitochondrial diseases (genetic disorders caused by mutations in the nuclear or mitochondrial genome) manifest through a remarkable clinical variation of symptoms in affected individuals, underlines the far-reaching implications of mitochondrial dysfunction. The study of mitochondrial function in genetic or non-genetic diseases therefore requires a multi-angled approach. Taking into account that the liver is among the organs richest in mitochondria, it stands to reason that, in the process of unravelling the pathogenesis of liver-related diseases, researchers give special focus to characterizing mitochondrial function. However, mitochondrial dysfunction is not a uniformly defined term. It can refer to a decline in energy production, increase in reactive oxygen species and so forth. Therefore, any study on mitochondrial dysfunction first needs to define the dysfunction to be investigated. Here, we review the alterations of mitochondrial function in liver cirrhosis with emphasis on acutely decompensated liver cirrhosis and acute-on-chronic liver failure (ACLF), the latter being a form of acute decompensation characterized by a generalized state of systemic hyperinflammation/immunosuppression and high mortality rate. The studies that we discuss were either carried out in liver tissue itself of these patients, or in circulating leukocytes, whose mitochondrial alterations might reflect tissue and organ mitochondrial dysfunction. In addition, we present different methodological approaches that can be of utility to address the diverse aspects of hepatocyte and leukocyte mitochondrial function in liver disease. They include assays to measure metabolic fluxes using the comparatively novel Biolog’s MitoPlates in a 96-well format as well as assessment of mitochondrial respiration by high-resolution respirometry using Oroboros’ O2k-technology and Agilent Seahorse XF technology.